Improving Communication and Coordination of Complex Perinatal Patients. Issue 3 (May 2015) - Gordon, Sara; Aydam, Joan; Hamm, Kenna; Rocha, Morgan; Northcut, Andrea; Roberson, Becky; Shook, Marilyn
<x xml:space="preserve">Abstract</x> Abstract Pregnant women with complex medical problems require comprehensive communication among members of their healthcare team. Using the Magnet Hospital model, our Patient and Perinatal Interprofessional Team at Seton Medical Center Austin focused on improving communication and patient satisfaction by initiating Perinatal Patient Care Conferences. Pregnant women with medical or obstetric complications and their families became a part of care plan development prior to admission to promote consistent communication and excellent care. We report our 7-year history of proactive meetings with pregnant women and their families in a nonclinical environment to discuss diagnosis, treatment, and prognosis. A collaborative written plan of care is developed that accommodates the woman's needs and wishes and is then disseminated among the healthcare team. This process has decreased women's and caregivers' anxiety and supported a culture of safety across the continuum of care.